A Method for Reducing the Impact of Range Ambiguity - Wei Min; Li Xiaobo; Wang Li (Leida xuebao, 2017)
In this paper, we study the clutter suppression problem of an airborne bistatic radar with range ambiguity and propose a novel method to reduce the impact of range ambiguity using geometric configuration. First, a clutter model, under any bistatic configuration is used to analyze the impact of range ambiguity. Second, a clutter equal-distance ring model of the airborne bistatic radar is established, and the relation between the geometric configuration and range ambiguity is analyzed. Third, the maximum pulse repetition frequency required to avoid range ambiguity is calculated. Simulation results show that the clutter suppression performance of an airborne bistatic STAP is greatly diminished with range ambiguity; however, this impact can effectively be reduced by selecting the appropriate radar configuration. Finally, simulation is performed to validate tests its validity.